Investigating the necessity of transferring patients, by sea or air, from four Healthcare Centers to a Secondary General Hospital in the South Aegean sea (2013 to 2016) - Anna Petrou; Marousso Balliou (Ene, 2019)
Introduction: The islands' primary healthcare services provide patient transportation and access to specialized healthcare services, which are not available locally. The early transfer and treatment of severely ill patients in organized healthcare facilities can improve their outcome and increase survival rates. Objective: To investigate the necessity of patients' transfer, by sea or air, from four Healthcare Centers of different islands, to a Secondary Hospital in South Aegean sea.Methods: Retrospective archive study investigating the necessity of 1329 patients' transfer from four regional Healthcare Centers to a secondary hospital in South Aegean sea during 2013 to 2016. Statistical analysis was performed with Microsoft Excel and SPSS 20 programs. There was a correlation of the subjects who were discharged on the next day of addition, with the lack of relevance of the transfer cause and discharge diagnosis (p <001). Results: Approximately one in three transferred patients was discharged the next day of transportation. In addition, for approximately one in two cases there was no affinity between the initial and discharge diagnosis. Finally, there was a high correlation of patients discharged on the day after transportation, with those without affinity between the two diagnosis (p <001). Conclusions: It appears that a large number of incidents were transported to the secondary hospital and were discharged the next day. This fact is very strongly correlated with the lack of relevance between the cause of transfer and discharge diagnosis. The revision of patients' transfer by private sea vessels, as well as the wide use of telemedicine, may contribute to reducing or even eliminating this phenomenon.